2017
DOI: 10.1111/cdoe.12349
|View full text |Cite
|
Sign up to set email alerts
|

Contextual and individual determinants of periodontal disease: Multilevel analysis based on Andersen's model

Abstract: Contextual predisposing factors and individual characteristics influenced periodontal disease experience in adults and older people. Contextual enabling factors were also meaningful determinants of periodontal disease in the former age group.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
31
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(35 citation statements)
references
References 30 publications
2
31
2
Order By: Relevance
“…However, it has been used as an analytical tool to investigate the association of environmental determinants and individual characteristics with a determined outcome or occurrence disease, due to the logic to select the associated contextual and individual factors. This can be seen in the study by Valente and Vettore, in 2018, that identified the relationship of such predictors with periodontal disease and considered the model useful to assess the contextual and individual influences on the condition.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…However, it has been used as an analytical tool to investigate the association of environmental determinants and individual characteristics with a determined outcome or occurrence disease, due to the logic to select the associated contextual and individual factors. This can be seen in the study by Valente and Vettore, in 2018, that identified the relationship of such predictors with periodontal disease and considered the model useful to assess the contextual and individual influences on the condition.…”
Section: Discussionmentioning
confidence: 99%
“…Association of contextual, individual determinants, and health behaviors with dental trauma, adapted from the behavioral model of Andersen…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The role of social determinants and contextual variables as potential factors influencing oral health have been studied; however, there is no consensus in literature regarding these factors [11,12]. A recent study, including data from the European Union and Israel, showed that the tooth retention in older adults may be related to socioeconomic status in early life, living conditions in childhood, and experiences in oral health throughout life [13].…”
Section: Introductionmentioning
confidence: 99%